Brain death induced renal injury. - Westendorp, W; Leuvenink, H; Ploeg, R (2011)
PURPOSE OF REVIEW: The considerable demand in kidney transplantation against a persisting organ donor shortage has forced most centers to nowadays accept of suboptimal donor kidneys. RECENT FINDINGS: Despite the substantial increase in the past decade in kidney transplantation with grafts retrieved from living donors and after donation from deceased brain dead (DBD) and extended criteria donation (ECD) donors, the supply of donor kidneys still does not meet the actual numbers needed. Moreover, older and more marginal kidney donors following the physiologically abnormal state of brain death do function less well and have a shorter graft survival. SUMMARY: In this review, we present an overview of the current knowledge of renal injury induced by pathophysiological effects of brain death and its relevance for renal transplant outcome.The better insight in the role of brain death induced renal injury has clearly demonstrated its detrimental effect on outcome but, also, offers new opportunities for donor management and evaluation of new biomarkers to assess kidney graft quality in the brain dead donor. The option to intervene and selectively block or enhance a pathway as well as identify specific parameters for graft quality at time of organ retrieval in the deceased brain dead donor will ultimately benefit early function and long-term survival.